THE EFFECTS OF DIGITAL PLATFORMS IN THE MUSIC INDUSTRY TO R&B MUSIC IN INDONESIA - Achmad Fauzan; Resky Cleverin; Standius Bara Prima Lumbaa (Sean Institute, 2023)
Music plays an essential role in forming the development of culture throughout the world. Music takes part in human’s everyday life, whether in the form of songs, films, televisions, advertisements and any other form, because it attracts attention and creates pleasure. Aside from the history, music has its own categorization called “genre”. Music genre is the grouping of music according to the similarities between each other. Music genres can be defined through music techniques, styles, contexts, rhythm, and themes. However, the existence of R&B music is still less popular in Indonesian society, and not even included in the top ten most preferred genre. Various reasons behind this facts might be because R&B is not easy-listening kind of music compared to Pop and another popular genre in Indonesia. Along with the development of technology, not only photo albums or videotapes are disappearing from the market, physical releases of music such as LPs and tapes are also increasingly difficult to find. Music streaming services has changed the industry of music. The history of music streaming services is start at 1993 with an online free music library called the Internet Underground Music Archive (IUMA). Spotify birth marked as the start of paid music streaming services as various online music streaming was also launch their services, such as Apple Music, Joox, and Deezer. Nowadays, listening to songs through streaming music services is become the new trend among youngster. Many music lovers start switching from listening to music from mp3 to streaming music services. With this trend, many streaming music application developers are competing to make their application to be the best. This research intends to pursue the rising influence of digital music streaming platforms on the genre of R&B music in Indonesia. because this research can be seen from a broader perspective, the researcher will only consider the effects of digital streaming to the Indonesian music industry. thus, this study will discuss on the lack of R&B music popularity.